Understanding Terence - Goldberg, Sander M. (Book collections on Project MUSE., 1986)
Instead of seeing Terence primarily as an adapter of Greek New Comedy, Sander Goldberg treats him as an innovative dramatist writing for a specifically Roman audience. His book will interest not only students of classical literature but also those concerned with wider problems of critical theory and the comic tradition. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.